Effects of different low temperature conditions on anaerobic digestion efficiency of pig manure and composition of archaea community. (22nd August 2022) - Gu, Shiyan; Wang, Ruji; Xing, Huige; Yu, Mingzhe; Shen, Siyu; Zhao, Liang; Sun, Jiyang; Li, Yi
Abstract: To explore the effect of low temperature on the anaerobic digestion of pig manure, the anaerobic digestion experiment was carried out under the conditions of inoculum concentration of 30% and TS of 8%. Five low-temperature gradients of 4, 8, 12, 16 and 20 °C were set to study the activities of gas production, pH, solluted chemical oxygen demand (SCOD), volatile fatty acids (VFAs), coenzymes F420 and archaea community composition in the digestion process. The results were demonstrated: as the temperature decreased, the more unstable the gas production became, the less gas production produced, and the later the gas peak occurred. There were no significant peaks at either 4 °C or 8 °C, and the SCOD was unstable over time. From 12 °C, the SCOD increased over time, and the higher the temperature, the faster the growth trend. The pH was always greater than 7.6. 8, 12, 16, 20 °C had different degrees of VFAs accumulation at the late digestion stage. The higher the temperature, the greater the amount of volatile acid accumulation. When the VFAs of each reactor reached the maximum, the proportion of acetic acid also reached the highest. The digestion system of the five treatment groups was dominated by hydrogen-nutrient methanogenic pathway. The results could provide a further reference for the mechanism of anaerobic digestion of pig manure at low temperatures. HIGHLIGHTS: Explore the mechanism of low temperature affecting anaerobic digestion from macro and micro perspectives. Five temperature gradients are set to explore how different low temperature conditions affect anaerobic digestion, providing a certain theoretical basis for engineering practice. Graphical Abstract